2013
DOI: 10.1038/cdd.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Y/CCAAT box in cancer: YB-1 (YBX1) or NF-Y?

Abstract: The Y box is an important sequence motif found in promoters and enhancers containing a CCAAT box -one of the few elements enriched in promoters of large sets of genes overexpressed in cancer. The search for the transcription factor(s) acting on it led to the biochemical purification of the nuclear factor Y (NF-Y) heterotrimer, and to the cloning -through the screening of expression libraries -of Y box-binding protein 1 (YB-1), an oncogene, overexpressed in aggressive tumors and associated with drug resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 138 publications
(151 reference statements)
2
93
1
1
Order By: Relevance
“…YBX1 functions as both a DNA and RNA binding protein and has been implicated in numerous cellular processes, including regulation of transcription and translation, premRNA splicing, DNA reparation, and mRNA packaging (36). YBX1 activation has been associated with cancer progression (37,38), the epithelial-mesenchymal transition (39), metastasis (40), and drug resistance (41,42). Western blot with a specific antibody confirmed that YBX1 is enriched in the TP53TG1 pull-down (Fig.…”
Section: Tp53tg1 Binds To the Rna Binding Protein Ybx1 And Prevents Itsmentioning
confidence: 93%
“…YBX1 functions as both a DNA and RNA binding protein and has been implicated in numerous cellular processes, including regulation of transcription and translation, premRNA splicing, DNA reparation, and mRNA packaging (36). YBX1 activation has been associated with cancer progression (37,38), the epithelial-mesenchymal transition (39), metastasis (40), and drug resistance (41,42). Western blot with a specific antibody confirmed that YBX1 is enriched in the TP53TG1 pull-down (Fig.…”
Section: Tp53tg1 Binds To the Rna Binding Protein Ybx1 And Prevents Itsmentioning
confidence: 93%
“…The sequence targeted by NF-Y [RRCCAAT(C/G)(A/G)] has long been known, thanks to numerous biochemical and genomic studies performed in mammals (Dolfini et al, 2009;Dolfini and Mantovani, 2013). By examining the NF-CO matrices ( Figures 2C and 3), one can notice a clear similarity to the NF-Y CCAAT matrix, RRCCAAT(C/G)(A/G), with a deviation of two nucleotides (underlined).…”
Section: Ccaat Versus Corementioning
confidence: 93%
“…This CCAAT motif is one of the most common cis-acting elements in the promoter and enhancer region of a large number of eukaryotic genes (47). Furthermore, this specific motif has been shown to be enriched in several genes overexpressed in a variety of cancers, including breast, colon, thyroid, prostate, and leukemia (48). However, its role in DN is not known.…”
Section: Nf-yc Regulates the Promoter Of The Mir-130bmentioning
confidence: 99%
“…Previously, our group demonstrated that miR-216a is induced by TGF-␤1 and mediates TGF-␤1-induced Akt kinase activation and collagen expression in MMC by targeting Ybx1 and Pten (49,50). Because Ybx1 also recognizes Y-box (CCAAT) (48), it is possible that the decrease of RIK and miR-130b is caused by miR216a-mediated down-regulation of Ybx1 (49) (Fig. 7).…”
Section: Rik-delmentioning
confidence: 99%